RETRACTED: Method for calculating the pyrolysis zone in the production unit activated carbon - Safin Rushan; Sotnikov Viktor (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001